Response of treated recycled aggregate concrete against low-velocity impact loading: Experimental and Weibull statistical analysis - Murali G.; Katman H.Y.B.; Wong L.S.; Ibrahim M.R.; Kathirvel P.; Abid S.R. (Elsevier Ltd, 2024)
Sustainable and ecologically friendly building practices require increased conservation and recycling of renewable resources. Because of the rise in development and demolition worldwide, using recycled construction materials as aggregate in new concrete can be an essential step towards making the material more environmentally friendly. Removing or fortifying the adherent mortar is the main technique to advance the poor standard of recycled concrete aggregate, which the adherent mortar causes. The study examines the impact performance of recycled aggregate concrete (RAC) comprising different replacement levels (10, 20, 30 and 40 %) of recycled aggregate (RA). Three concentrations (10, 15, and 20 %) of MgSO4 solution were used to pre-treat the RA and subjected to three different immersion times of 5, 10, and 15 days. For this, thirty-seven mixtures were prepared with the combination of RA contents, MgSO4 concentrations and immersion periods. The study was divided into three phases. The physical properties of RA, slump, and compressive strength tests were studied in the first phase. The best thirteen mixtures that exhibited expectational results in the first phase are put forward to the second phase. The effect of RA content, MgSO4 concentration and immersion periods on the impact strength was studied in the second phase. Besides, the differences in the impact test results were studied by Weibull distribution and results were displayed with regard to the probability of survival. The final phase studied the impact response of reinforced concrete slabs under a large mass impact. The findings reveal that the five days of immersion in a 10 % MgSO4 solution has been shown to enhance the impact strength of RAC, whereas a replacement ratio of 20 % is recommended. 2023 Elsevier Ltd